Clubbing in trade policies: How much a threat to the multilateral constitution? - Barbara Dluhosch; Daniel Horgos (Constitutional Political Economy, 2023)
Preferential trade agreements (PTAs) have mushroomed over the last decades. However, the various forms of bi- and plurilateral arrangements have always been met with the concern that their proliferation might come at the expense of overall trade freedom because of undermining multilateral governance. This paper starts from the fact that international treaties are notoriously difficult to enforce, as is compliance with (trade) agreements. By focusing on the political economy of how cooperation in trade liberalization is ultimately sustained via the threat of retaliation as institutionalized within the World Trade Organization (WTO), the paper illuminates a novel and completely different channel between PTA membership and multilateral trade liberalization. Exploring their interaction with respect to trade freedom, we explain that PTA membership actually improves on the working of multilateral arrangements that are supposed to ensure cooperation in trade liberalization, thus effectively catering to more open trade.
Keywords: F13; F51; C73; D02; 330; International political economy; World trade constitution; Trade liberalization; Compliance